A.) (x+1)(x-2)+(x+2)(x-1) =
b.) (5k+n)(k-2n)-k(4k+n) =
c.) (4y+3)(y-2)-2y(4-2y) =
d.) -(3c-2)(c-1)-c(c-2) =
e.) 2(3a²-1)-(a+2)(a+2) =
f.) 5x²(x²+1)-(x²-2)(x²+3) =

Sorki że tak mało pkt. ale nie mam więcej... Wybiore najlepsze rozwiązanie... ;-)

2

Odpowiedzi

2009-12-09T20:52:57+01:00
A.) (x+1)(x-2)+(x+2)(x-1) =x²-2x+x-2+x²-x+2x-2=2x²-4=2(x²-2)
b.) (5k+n)(k-2n)-k(4k+n) =5k²-10kn+nk-2n²-4k²-kn=k²-11kn=k(k-11n)
c.) (4y+3)(y-2)-2y(4-2y) =4y²-8y+3y-6-8y+4y²=8y²-13y-6
d.) -(3c-2)(c-1)-c(c-2) =-(3c²-3c-2c+2)-c²+2c=-3c²+3c+2c-2-c²+2c=-4c²+7c-2
e.) 2(3a²-1)-(a+2)(a+2) =6a²-2-(a²-4)=6a²-2-a²+4=5a²+2
f.) 5x²(x²+1)-(x²-2)(x²+3) =5x4+5x²-(x4+3x²-2x²-6)=5x⁴+5x²-x⁴-3x²+2x²+6=4x⁴+4x²+6
2009-12-09T21:33:34+01:00
A.) (x+1)(x-2)+(x+2)(x-1) =x²-2x+1x-2+x²-1x+2x-2=2x²-4


b.) (5k+n)(k-2n)-k(4k+n) =5k²-10kn+kn-2n²-4k²-kn=k²-2n²-10kn

c.) (4y+3)(y-2)-2y(4-2y) =4y²-8y+3y-6-8y+4y²=8y²-13y-6


d.) -(3c-2)(c-1)-c(c-2) =-(3c²-3c-2c+2)-c²+2c=-3c²+5c+2-c²+2c=-4c²+7c-2

e.) 2(3a²-1)-(a+2)(a+2) =6a²-2-(a²+2a+2a+4)=6a²-2-a²-4a-4=5a²-4a-6


f.) 5x²(x²+1)-(x²-2)(x²+3) =5xdo4+5x²-(xdo4+3x²-2x²-6)=5xdo4+5x²-xdo4-3x²+2x²+6=4xdo4+4x²+6